Composição florística e estimativa de biomassa em lianas em áreas de manejo florestal no Sul da Amazônia - Santos, Márcia Cléia Vilela dos (2016)
Lianas are important components of tropical forest structure, not only because they play an important role in the total biomass and carbon storage, but also because they add a significant amount of plant biodiversity to the forest composition. They are rarely studied in the transitional forests between Cerrado and Amazon rainforest in Brazil. To test the hypothesis that in these transitional forests, the tree structure defines the liana distribution patterns in managed areas, we posed two main questions: 1. What are the dominant species of lianas (stem number) among sites with different post-management ages? 2. Is species density of lianas associated with density and/or basal area of the trees? Liana collections and censuses were carried out from March 2011 to January 2013 in three areas with different historical anthropogenic disturbance in southern Amazonia. We sampled 20 permanent plots of 40 x 250m following the methodology used in the Research Program in Biodiversity (RAPELD). Lianas were sampled in two tracks of different widths, depending on the diameter class. Stems with diameter (DBH) ≤ 4.9 cm were sampled in a track 10 m wide, with 5 m to either side of a center line, whereas liana stems with DBH ≥ 5 cm were sampled in an overlapping track 40 m wide, with 20 m on each side the center line. We sampled 7890 liana individuals in 133 species, 77 genera, and 37 families. Thirtenn species are endemic to Brazil, and 18 were recorded for the first time in the state of Mato Grosso. Of individuals sampled at the three sites, 6530 had stems ≤ 4.9cm, 1360 had stems ≥ 5 cm in diameter (17% of the total) and of these, only 276 had stems ≥ 10 cm diameter (3.5% of the total). The three most important species, as determined by number of stems and the importance value index were: Deguelia negrensis, Abuta rufescens and Uncaria guianensis. The model (GLM) determined using sites as indicators of time-since-regeneration shows that liana structure responds via colonization patterns directly linked to arboreal vegetation structure.